1987
DOI: 10.1172/jci113209
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines mediate uncontrolled calcium entry and cell damage in rat heart in the calcium paradox.

Abstract: Brief perfusion of heart with calcium-free medium renders myocardial cells calcium-sensitive so that readmission of calcium results in uncontrolled Ca2+ entry and acute massive cell injury (calcium paradox). We investigated the hypothesis that polyamines may be involved in the mediation of abnormal Ca2+ influx and cell damage in the calcium paradox. The isolated perfused rat heart was used for these studies. Calcium-free perfusion promptly (< 5 min) decreased the levels of polyamines and the activity of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…How neuronal activity induces ODC1 is not clearly understood but in peripheral tissue there is evidence of a physiological coupling between polyamine levels and intracellular calcium (Ca 2+ ) concentrations (Chang, 1991; Koenig et al, 1987; Langdon et al, 1984). In a pioneer study of a phenomenon called the calcium paradox, Koening et al linked Ca 2+ and polyamines with excitability and pathological consequences of maladaptive homeostatic mechanisms in the heart (Koenig et al, 1987).…”
Section: Polyamines In Activity-feedback Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…How neuronal activity induces ODC1 is not clearly understood but in peripheral tissue there is evidence of a physiological coupling between polyamine levels and intracellular calcium (Ca 2+ ) concentrations (Chang, 1991; Koenig et al, 1987; Langdon et al, 1984). In a pioneer study of a phenomenon called the calcium paradox, Koening et al linked Ca 2+ and polyamines with excitability and pathological consequences of maladaptive homeostatic mechanisms in the heart (Koenig et al, 1987).…”
Section: Polyamines In Activity-feedback Mechanismsmentioning
confidence: 99%
“…In a pioneer study of a phenomenon called the calcium paradox, Koening et al linked Ca 2+ and polyamines with excitability and pathological consequences of maladaptive homeostatic mechanisms in the heart (Koenig et al, 1987). Koening et al (1987) demonstrated that changes in ODC1 activity and polyamine concentrations followed changes in intracellular Ca 2+ concentration ([Ca 2+ ]) with a time delay of approximately 15 seconds.…”
Section: Polyamines In Activity-feedback Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, reperfusion injury, or that which occurs during reperfusion of previously ischemic tissue, has not yet been defined. Although normally characterized in the intact heart (Koenig et al, 1987;Uemura et al, 1985), little evidence exists for such a phenomenon in single cells of a number of excitable tissues (Li et al, 1988;Young, 1986). Conceptually, however, the term "calcium paradox" injury has been 01992 Wiley-Liss, Inc. associated with deleterious reperfusion phenomena in both the myocardium and central nervous system (Young, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Interest has focused on spermine and spermidine as potential neuromodulators of the NMDA receptor complex in brain; specifically, the binding of (+)-5-[3H]methyl-10,11-dihydro-5H-dibenzo [a,d]cyclohepten-5,10-imine maleate ([3H]MK-801), N-(1-[2-thienyl]cyclohexyl)-3,4-[ 3H]piperidine ([3H]TCP), and [3H]glycine to the NMDA receptor complex was enhanced by polyamines (Ransom and Stec, 1988), and the effect was blocked by arcaine, agmatine, diethylenetriamine, and 1,8-octanediamine, structurally related analogues of spermine and spermidine (Reynolds, 1990;Sacaan and Johnson, 1990;Williams et al, 1990). Furthermore, spermine and spermidine are considered to be intracellular messengers that increase free cytosolic Ca 2+ levels by stimulating Ca 2+ influx and mobilizing Ca 2+ from intracellular sites in both brain (Igbal and Koenig, 1985 ;Bondy and Walker, 1986) and other tissues (Koenig et al, 1983(Koenig et al, , 1987 .…”
mentioning
confidence: 99%